Land sharing is essential for snow leopard conservation. (November 2016) - Johansson, Örjan; Rauset, Geir Rune; Samelius, Gustaf; McCarthy, Tom; Andrén, Henrik; Tumursukh, Lkhagvasumberel; Mishra, Charudutt
Abstract: Conserving large carnivores in an increasingly crowded planet raises difficult challenges. A recurring debate is whether large carnivores can be conserved in human used landscapes (land sharing) or whether they require specially designated areas (land sparing). Here we show that 40% of the 170 protected areas in the global range of the snow leopard ( Panthera uncia ) are smaller than the home range of a single adult male and only 4–13% are large enough for a 90% probability of containing 15 or more adult females. We used data from 16 snow leopards equipped with GPS collars in the Tost Mountains of South Gobi, Mongolia, to calculate home range size and overlap using three different estimators: minimum convex polygons (MCP), kernel utility distributions (Kernel), and local convex hulls (LoCoH). Local convex hull home ranges were smaller and included lower proportions of unused habitats compared to home ranges based on minimum convex polygons and Kernels. Intra-sexual home range overlap was low, especially for adult males, suggesting that snow leopards are territorial. Mean home range size based on the LoCoH estimates was 207 km 2 ± 63 SD for adult males and 124 km 2 ± 41 SD for adult females. Our estimates were 6–44 times larger than earlier estimates based on VHF technology when comparing similar estimators, i.e. MCP. Our study illustrates that protected areas alone will not be able to conserve predators with large home ranges and conservationists and managers should not restrict their efforts to land sparing. Highlights: Snow leopards had substantially larger home ranges than previously reported. Snow leopard home ranges were exclusive with little overlap. Only a few protected areas across Asia are large enough to sustain 15 females. Snow leopard conservation requires a land sharing approach.